Pengaruh Penggunaan Media Sepin terhadap Kemampuan Bahasa Anak Tk Daarul Hayah Kota Pagar Alam - Haryani, Meti; Amin, Alfauzan; Eka Citra Dewi, Desi (UIN Fatmawati Sukarno Bengkulu, 2025)
Language development is a crucial part of a child's development. In early childhood, learning can be carried out by utilizing concrete objects and learning media in the surrounding environment so that it can improve children's language skills. In Daarul Hayah Kindergarten, Pagar Alam, in group B, there are still many children who are less brave to ask questions and tend to be passive during the learning process. This is because the learning process is generally still conventional, the learning media used is still less varied and possibly less interesting for children. Sepin media is one of the media that can be used to improve children's language skills. Therefore, this study aims to see the extent of the influence of the use of Sepin media to improve the language skills of early childhood. This research is an experimental study. The experimental design used in this study is a quasi-experimental study, with a Pretest-Posttest Control Group Design. This research was conducted in 2 classes of Daarul Hayah Kindergarten, Pagar Alam City in the second semester from February to March 2025. The population in this study were all children of Daarul Hayah Kindergarten, Pagar Alam City, group B. The sample in this study was class B1 as the experiment and class B2 as the control class. Data collection techniques used interviews, observation, and documentation. Data analysis techniques used homogeneity tests and hypothesis testing. This study resulted in the influence of the use of SEPIN media on children's language skills at Daarul Hayah Kindergarten. Where the post-test scores calculated for the hypothesis test were shown in the experimental group and the control group. The average post-test score for the SEPIN media group was 17.5 (high) and the average post-test score for the group without SEPIN media was 13.9 (moderate) for children's language skills. This was proven by a t-test analysis: at a significance level of 0.05, the experimental class's value was tcount = 26.077, and the t-table obtained at dk 13 was ttable = 2.16037. This calculation revealed that tcount>ttable; thus, the findings are substantive.